Sampling Dan Pengamatan Perubahan Penutupan Makro Algae Pada Kondisi Pra-Upwelling Dan Upwelling - Modesta Ranny Maturbongs (AGRICOLA, 2015)
This study aims to present a sampling technique, making dried herbarium and observation of macro algae cover change in different water conditions, when the pre-conditions of upwelling and upwelling. Samples taken at the study site using line transect method quadrant, the use of 0.5 x 0.5 m quadrant for data percentage cover of macro algae. From the research found 3 classes, 12 orders, 17 families, 23 genera and 33 species with class composition is dominated by the 56% class Rhodophyceae, Chlorophyceae 25%, and the class Phaeophyceae few are found at 19%. Macroalgae closing percentage is very low in pre-upwelling conditions particularly in May with total closing low of 33.9%, and increased every month in upwelling conditions, peak in August amounted to 97.8%.